2021
DOI: 10.1007/s40279-021-01550-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Landing Patterns in Jumping Athletes Associated with Patellar Tendinopathy? A Systematic Review with Evidence Gap Map and Meta-analysis

Abstract: Background Patellar tendinopathy (PT) is common and debilitating for jumping athletes. Intriguingly, despite its high prevalence and many research studies, a causal explanation for PT presence remains elusive. Objective Our objective was to investigate whether landing biomechanics among jumping athletes are associated with PT and can predict onset. Methods We conducted a systematic review with evidence gap map and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…An evidence gap map was created to provide an overview of the evidence available investigating trunk biomechanics in individuals with knee disorders. The evidence gap map allows the identification of outcomes with sufficient or insufficient evidence due to the number of similar studies [ 41 ]. For the presentation of the evidence, all data were grouped according to measurement method, planes of motion, outcome, and task categories as previously mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…An evidence gap map was created to provide an overview of the evidence available investigating trunk biomechanics in individuals with knee disorders. The evidence gap map allows the identification of outcomes with sufficient or insufficient evidence due to the number of similar studies [ 41 ]. For the presentation of the evidence, all data were grouped according to measurement method, planes of motion, outcome, and task categories as previously mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…11 Jump-landing biomechanics have the potential to detect risky movement patterns in terms of suboptimal patellar tendon loading. 9,12,13 Only three studies explicitly investigated patellar tendon loading during jump-landing tasks and found protective strategies including reduced peak patellar tendon forces and/or loading rate in subjects with current symptoms of PT. 8,14,15 On the other hand, fatigue is considered to be a major extrinsic risk factor for knee injuries, primarily by modulating other intrinsic risk factors for lower extremity injuries such as jump-landing biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, suboptimal tendon loading should be monitored carefully, certainly in case of non‐uniform muscle‐tendon adaptations (e.g., adolescent athletes) 11 . Jump‐landing biomechanics have the potential to detect risky movement patterns in terms of suboptimal patellar tendon loading 9,12,13 . Only three studies explicitly investigated patellar tendon loading during jump‐landing tasks and found protective strategies including reduced peak patellar tendon forces and/or loading rate in subjects with current symptoms of PT 8,14,15 …”
Section: Introductionmentioning
confidence: 99%
“…The second study only recorded vertical jump height and concluded that great jumping ability was a risk factor for developing patellar tendinopathy, which is not meaningful to the injury prevention (Visnes et al, 2013 ). High-quality prospective studies with larger sample sizes and more rigorous study designs are essential to definitively determine whether landing biomechanics play a role in the development of patellar tendinopathy (Tayfur et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%